2000
DOI: 10.1111/j.1528-1157.2000.tb04612.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Intracarotid Amobarbital Procedure Predict Global Amnesia After Temporal Lobectomy?

Abstract: Summary: Purpose: The intracarotid amobarbital procedure (IAP) is widely used to help predict who might be at risk for postoperative amnesia after unilateral temporal lobectomy for intractable seizures. We describe the memory outcome in 10 patients who underwent standard temporal lobectomy, including mesial temporal structures, despite failing the memory portion of the IAP after injections both ipsilateral and contralateral to the resected seizure focus.Methods: Data for seven of the study subjects were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The superselective Wada test via the anterior choroid artery with its functional inactivation of only mesial parts of the temporal lobe without accompanying aphasia, attentional, and behavioral disturbances allows a valid prediction of postoper- ative global memory performance. In agreement with other authors [7] we conclude that this better memory prediction in our case was possible because the patient was not impaired by aphasia and attentional disturbances during the superselective Wada test.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The superselective Wada test via the anterior choroid artery with its functional inactivation of only mesial parts of the temporal lobe without accompanying aphasia, attentional, and behavioral disturbances allows a valid prediction of postoper- ative global memory performance. In agreement with other authors [7] we conclude that this better memory prediction in our case was possible because the patient was not impaired by aphasia and attentional disturbances during the superselective Wada test.…”
Section: Discussionsupporting
confidence: 79%
“…Some authors pointed to the incomplete perfusion of the hippocampus [5], and there are empirical findings of false positive and false negative identifications of patients at risk for postoperative anterograde amnesia [1,2,7,8]. In a recent study with intrahippocampal depth electrodes and SPECT, Urbach et al [17] demonstrated that increased EEG delta activity in the posterior hippocampus could be observed even if only the anterior part of the hippocampus is perfused by amobarbital.…”
Section: Discussionmentioning
confidence: 99%
“…Kubu et al [22] reported 10 patients with bilateral failure on Wada testing who did not develop amnesia following ATL. Lacruz et al [11] reported that the patients with a failed Wada test did not develop significant memory decline after temporal lobectomy or selective amygdalohippocampectomy.…”
Section: Discussionmentioning
confidence: 98%
“…While many studies have shown that the Wada test was helpful in predicting the decline in material-specific memory following unilateral ATL [6,11,12,[18][19][20], others have not been able to substantiate its usefulness in this respect [8,[21][22][23][24]. Several factors contribute to the lack of consensus in the literature regarding the predictive value of the Wada memory test.…”
Section: Introductionmentioning
confidence: 92%
“…3 Such patients illustrate that localization of cortical function may not be as precise as we might suppose, especially in individuals whose brain function is altered by disease. Often not considered when predicting the effect of surgery is the effect of a successful operation on cortical function.…”
mentioning
confidence: 96%